2-(4-Oxo-1,3-thiazolidin-2-ylidene)acetamid as promising scaffold for designing new antifungal compounds - Konstantin L. Obydennov; Tatiana A. Kalinina; Daria V. Ryabova; Maria F. Kosterina; Tatiana V. Glukhareva (Chimica Techno Acta)
1,3-Thiazolidin-4-one derivatives with a exocyclic C=C double bond in position 2 of the hetero ring have a wide spectrum of biological activity, but their fungicidal activity has not been studied as much as it should be. This paper presents a simple and convenient approach for obtaining potential antifungal agents based on 2-(4-oxo-1,3-thiazolidin-2-ylidene)acetamides. The first examples of evaluating the fungicidal activity of 8 obtained compounds on 8 strains of phytopathogenic fungi are presented. A highly active compound 4e with EC50 of 0.85 and 2.29 µg/mL against A. solani and P. lingam, respectively, was found to be promising for further study.